Extraction of Buildings from QuickBird Imagery for Municipal Use – the Relevance of Urban Context and Heterogeneity - Freire, S. (2011)
Lisbon is both a historical and modern city having a dynamic landscape, where increasingly diverse urban forms and materials coexist. This complex reality is possibly causing the feature extraction process from imagery to become more challenging. This study tests the semi-automated extraction of buildings from a QuickBird image in urban areas with different characteristics, and explores the impact of the heterogeneity of these features in the extraction process. Spatial metrics are used to characterize types of buildings present in the study areas. Results show that the study areas display different levels of heterogeneity even for the same type of building and suggest that the extraction may be affected by the spatial configuration of target features.